VALIDATION OF THE H. HOTTEL- R.J. TUCKER METHOD FOR THE ESTIMATION OF THE PERFORMANCE OF A FURNACE IN A THREEBED REGENERATIVE OXIDIZER THAT NEUTRALIZES GASEOUS POLLUTANTS - Pittas, Nicholas; Margaris, Dionissios; Georgiou, Demos; Grapsa, Theodoula (International Journal of Engineering Technologies and Management Research, 2018)
This paper investigates the validity of the method of zones proposed by H. Hottel and R. J. Tucker for enclosures with surfaces exposed to significant thermal radiation. The analysis is focused on a specific combustion chamber in a three-bed regenerative oxidizer and calculates the temperatures and the corresponding thermal flux exchanges among the hot wall surfaces of the chamber. The temperature distribution and the initial composition of the gaseous mixture at the inlet plane were assumed known.